INSTITUTIONAL MECHANISMS FOR THE IMPLEMENTATION OF ANTI-CORRUPTION POLICY IN UKRAINE: PROBLEMS AND PROSPECTS - HRONSKYI, Serhii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the institutional mechanisms of anti-corruption policy implementation in Ukraine, focusing on their current state, key challenges, and prospects for improvement. Based on institutional and systemic approaches, the study analyzes the activities of specialized bodies such as the National Anti-Corruption Bureau of Ukraine (NABU), the National Agency on Corruption Prevention (NACP), the Specialized Anti-Corruption Prosecutor’s Office (SAPO), the High Anti-Corruption Court (HACC), and the Asset Recovery and Management Agency (ARMA), as well as digital instruments of transparency, including the electronic declaration system, Prozorro, Prozorro.Sale, and the DREAM platform. The article outlines the dynamics of institutional development during 2023–2025, highlighting the reintroduction of public access to asset declarations, the first independent audit of NABU, the reform of ARMA, and the scaling of DREAM as a nationwide reconstruction monitoring tool. Particular attention is paid to structural weaknesses, such as political vulnerability of anti-corruption bodies, legal inconsistencies, the excessive workload of the judicial system, deficiencies in asset management, and persistently low levels of public trust. A comparative analysis of international experience (Romania, Singapore, Hong Kong, the United States, EU member states) demonstrates that institutional independence, harmonized legal frameworks, procedural efficiency, and digital transparency are decisive conditions for effective anti-corruption policy. For Ukraine, the key prospects lie in strengthening the autonomy of specialized bodies, aligning public procurement legislation with the acquis communautaire, integrating digital platforms into a unified transparency ecosystem, optimizing the functioning of the High Anti-Corruption Court, and fostering a culture of integrity in both public administration and civil society.
Keywords: anti-corruption policy; institutional mechanisms; NABU; NACP; SAPO; HACC; ARMA; Prozorro; DREAM; public procurement; acquis communautaire; international experience; integrity